WAIS Divide Sonic Log Data - Waddington, Edwin D.; Matsuoka, Kenichi; Kluskiewicz, Dan; Mccarthy, Michael; Anandakrishnan, Sridhar (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This data set contains a record of speeds for vertically-propagating compression-waves measured throughout the depth of ice that surrounds the WAIS-D borehole. Multiple logs provide redundant measurements for all depths. Data for individual wave-speed measurements were included, as well as 3 m running averages for each log. A Takeaway Profile that represents our interpretation of the combined data set is also included.